Antioxidant effect of fat-soluble rosemary and green tea extracts on storage period prolongation of meat paste - Topchiy, Oksana; Kotlyar, Eugene; Pasichnyi, Vasyl; Shevchenko (Kishenko), Iryna; Tymchuk, Alla; Kryzhova (Vengliyk), Julia; Petrina, Alla; Dets, Nadiia (My University, 2021)
Intensive development of the food market necessi-tates its research, structuring in order to identify ways to create new products with improved quality charac- teristics, in particular meat pates, and prolongation of their storage period by adding fat-soluble rosemary and green tea extracts. Meat pates are manufactured using liver and blanched chicken fillet, pork fat blend and refined deodorized sunflower oil with extracts from Danisco (Denmark) in an amount of 10%. The following blends have been developed: blend (50 : 50) of pork fat and refined de- odorized sunflower oil with the rosemary extract ad- dition of 0.1%; blend (50 : 50) of pork fat and refined deodorized sunflower oil with the green tea extract addition of 0.05% and blend (50 : 50) of pork fat and refined deodorized sunflower oil with the green tea and rosemary extract addition of 0.15%. Sensory eval- uation research of hydrolytic and oxidative processes during products storage have been carried out for aim achievement, namely, the changes in quality indicators of the test samples were recorded during the storage period until the critical value of the peroxide number (10 mmol½О/kg) was reached. The acid number has been determined as an indicator of hydrolytic putre- faction degree. Compositions and technologies for the blends pro- duction using plant extracts of various concentrations for meat pates have been developed. The oxidative processes dynamics and resistance to damage during products storage have been determined. The storage period of all blends is 50 days, against the generally accepted storage period for fats in an open container - 30 days. The research results have confirmed that the quality indicators of the products are attributable to the specified requirements. The antioxidant and bactericidal properties of fat-solu- ble extracts have been established. It has been proven that the use of rosemary and green tea extracts, and especially their combination, helps to increase the meat pates stability, expand the product line and in-crease their safety for consumers. Інтенсивний розвиток продовольчого ринку зумовлює необхідність його дослідження, структуризації з метою визначення шляхів створення нових продуктів із покращенням якісних характеристик, зокрема м’ясних паштетів, та подовження терміну їх зберігання за рахунок додавання жиророзчинних екстрактів розмарину та зеленого чаю. . Для виготовлення м’ясних паштетів використовується печінка та бланшоване куряче філе, суміш свинячого жиру та олії соняшникової рафінованої дезодорованої з додаванням екстрактів Danisco (Данія) у кількості 10%. Розроблено такі суміші: суміш (50 : 50) свинячого жиру та олії соняшникової рафінованої дезодорованої з додаванням екстракту розмарину 0,1 %; суміші (50 : 50) свинячого жиру та олії соняшникової рафінованої дезодорованої з додаванням екстракту зеленого чаю 0,05 % та суміші (50 : 50) жиру свинячого та олії соняшникової рафінованої дезодорованої з додаванням зеленого чаю та екстракту розмарину 0,15 %. Для досягнення поставленої мети проведено сенсорні дослідження гідролітичних та окислювальних процесів під час зберігання продукції, а саме – реєстрацію зміни показників якості дослідних зразків протягом терміну зберігання до досягнення критичного значення перекисного числа (10 ммоль½О/ кг) було досягнуто. Визначено кислотне число як показник ступеня гідролітичного гниття. Розроблено композиції та технології виготовлення сумішей з рослинними екстрактами різної концентрації для м’ясних паштетів. Визначено динаміку окислювальних процесів та стійкість до пошкоджень під час зберігання продукції. Термін зберігання всіх сумішей - 50 діб, проти загальноприйнятого терміну зберігання жирів у відкритій тарі - 30 діб. Результати досліджень підтвердили, що показники якості продукції відповідають заданим вимогам. Встановлено антиоксидантні та бактерицидні властивості жиророзчинних екстрактів. Доведено, що використання екстрактів розмарину та зеленого чаю, а особливо їх поєднання, сприяє підвищенню стійкості м’ясних паштетів, розширенню асортименту та підвищенню їх безпеки для споживачів.
Keywords: кафедра технології м’яса і м’ясних продуктів; кафедра технології молока і молочних продуктів; meat pastes; fat-soluble green tea extract; fat-soluble rosemary extract; blend; oxidation; м'ясні паштети; жиророзчинний екстракт зеленого чаю; жиророзчинний екстракт розмарину; суміш; окислення